Building an Ecologically valid, Large-scale Diagram to Help Developers Stay Oriented in Their Code - Cherubini, Mauro; Venolia, Gina; DeLIne, Robert (VLHCC '07 Proceedings of the IEEE Symposium on Visual Languages and Human-Centric Computing, 2007)
This paper presents the creation, deployment, and evaluation of a large-scale, spatially-stable, paper-based visualization of a software system. The visualization was created for a single team, who were involved systematically in its initial design and subsequent design iterations. The evaluation indicates that the visualization supported the "onboarding" scenario but otherwise failed to realize the research team's expectations. We present several lessons learned, and cautions to future research into largescale, spatially-stable visualizations of software systems.